Common Characteristics and Clinical Management Recommendations for Juvenile Recurrent Parotitis: A 10-Year Tertiary Center Experience. Issue 1 (February 2022) - Benaim, Ezer; Fan, Timothy; Dash, Anwesh; Gillespie, M. Boyd; McLevy-Bazzanella, Jennifer
Objective: Juvenile recurrent parotitis (JRP) is a rare disease that may adversely affect normal development and quality of life. The objective of this study was to report on the demographics, characteristics, and treatment outcomes of JRP and to offer evidence-based management recommendations. Study Design: Retrospective review. Setting: A single tertiary care pediatric teaching hospital. Methods: Medical records, imaging studies, and laboratory findings over a 10-year period were retrospectively collected and reviewed, resulting in 41 patients with JRP between the ages of 8 months and 16 years. Results: Black males aged 2 to 8 years were most commonly affected by JRP. Overall, 18 (44%) patients received ≥3 antibiotics, and 17 (42%) underwent sialendoscopy for treatment. Over 75% of patients had no JRP recurrences after 3 sialendoscopies. The most common imaging approach was computed tomography (42%), and the most frequent laboratory results were elevated amylase (83%) and C-reactive protein (82%). Atopy (61%) and excess weight (42%) were routinely associated with JRP, especially in severe cases. Conclusion: JRP workup and treatment plans should begin with the least burdening modalities, including over-the-counter analgesics, minimal laboratory studies in the acute phase, and ultrasonography over computed tomography. Clindamycin is an effective initial antibiotic of choice, and severe recurrences may be controlled with sialendoscopy. Optimizing the health of patients with JRP includes managing comorbidities, especially of atopic and overweight origins, which are associated with more severe cases.